Teknik dan Penyusunan Insrumen Evaluasi Kognitif - ., Syahri; pengelola, pengelola (Tasyri` : Jurnal Tarbiyah-Syari`ah-Islamiyah, 2021)
In the learning process, evaluation is needed to know the learning results obtained by learners to develop their potential both knowledge (cognitive), attitude (affective), and skills (Psychmotor). The most basic thing that must be seen is in terms of knowledge (Cognitive). To make a good assessment in terms of knowledge, techniques and ways of preparing good instruments are also needed, especially in terms of knowledge (cognitive). In this scientific work will be discussed several techniques and preparation of knowledge evaluation (cognitive) including: a) Steps for The Preparation of Instruments Assessment of Learning Outcomes of Knowledge/Cognitive, b) Techniques for The Preparation of Learning Outcome Tests of Knowledge / Cognitive, and c) Non-Test Techniques for Assessment of Learning Outcomes of Knowledge / Cognitive Based on analysis of steps of preparing cognitive domain instruments, among others: 1) Defines the purpose and region of the test, 2) Outlines the material and behavioral limits to be measured, 3) Arranges a grid grid, 4) Selects the form of the test, 5) Determines the length of the test.